2005
DOI: 10.1128/jvi.79.13.8361-8373.2005
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus UL130 Protein Promotes Endothelial Cell Infection through a Producer Cell Modification of the Virion

Abstract: Human cytomegalovirus (HCMV) growth in endothelial cells (EC) requires the expression of the UL131A-128 locus proteins. In this study, the UL130 protein (pUL130), the product of the largest gene of the locus, is shown to be a luminal glycoprotein that is inefficiently secreted from infected cells but is incorporated into the virion envelope as a Golgi-matured form. To investigate the mechanism of the UL130-mediated promotion of viral growth in EC, we performed a complementation analysis of a UL130 mutant strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 48 publications
4
73
0
Order By: Relevance
“…Previous reports regarding the function of pUL130 suggested that this protein might be critical for formation of the pentameric gCIII complex. The C-terminal frameshift naturally occurring in HCMV strain Towne has been reported to cause accelerated lysosomal degradation of pUL130 compared to the wild-type protein (15), and lack of the UL130 protein results in loss of the complete pentameric complex from the virion envelope (21). It was therefore tempting to speculate that the Cterminal UL130 mutations that reduced EC tropism in our analysis also affected incorporation of this complex into mutant virions.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous reports regarding the function of pUL130 suggested that this protein might be critical for formation of the pentameric gCIII complex. The C-terminal frameshift naturally occurring in HCMV strain Towne has been reported to cause accelerated lysosomal degradation of pUL130 compared to the wild-type protein (15), and lack of the UL130 protein results in loss of the complete pentameric complex from the virion envelope (21). It was therefore tempting to speculate that the Cterminal UL130 mutations that reduced EC tropism in our analysis also affected incorporation of this complex into mutant virions.…”
Section: Resultsmentioning
confidence: 92%
“…1). The first charge cluster was omitted because amino acids 1 to 25 have been shown to be a signal peptide that is cleaved off (15 The generation of mutants was performed in E. coli by markerless replacement of the selected charged amino acids with alanines in BACs containing the genome of the highly endotheliotropic HCMV-TB40-BAC4. A complete list of the generated mutants and the respective amino acid exchanges as well as the primer sequences used for markerless mutagenesis are given in Tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, entry into epithelial, endothelial, dendritic, and monocytic cells requires gB, gH/gL/gO, and the PC and occurs through endocytosis or macropinocytosis followed by a pH-dependent fusion event (Fig. 3B) (31-33, 35,[44][45][46][47][48][49]. The stark difference in CMV entry pathways underscores the involvement of fundamentally distinct entry mechanisms that likely extend beyond mere differences in cell-type-specific receptors.…”
Section: Glycoprotein Components Of the CMV Virionmentioning
confidence: 99%
“…The evaluation of the chimeras is now in an investigator-initiated phase I study to evaluate safety and immunogenicity properties in CMV-naive subjects. A different 'dial-up' strategy seeks to improve the AD169 LACV by repairing mutations that prevent expression of the gH pentamer complex, 108,109 with the intention of broadening cell tropism and the quality of neutralizing antibody responses. One challenge is the loss of gH pentamer expression during propagation in fibroblasts, 110,111 so the LACV candidate V160 must be propagated on the ARPE19 109,112 epithelial cell line.…”
Section: Live Attenuated Virus Vaccinementioning
confidence: 99%